2018
DOI: 10.2147/dmso.s187092
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan is effective to ameliorate metabolic syndrome in rat model – a preclinical report

Abstract: BackgroundMetabolic syndrome (MS) is known to be associated with hypertension, insulin resistance, and dyslipidemia, and it raises the risk for cardiovascular diseases and diabetes mellitus. Telmisartan is used in clinic as an angiotensin II receptor blocker and it is also identified as activating peroxisome proliferator-activated receptors δ (PPARδ). Activation of PPARδ produced beneficial effects on fatty acid metabolism and glucose metabolism. This study aims to investigate the effects of telmisartan on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The lack of differences in food intake, urine output and creatinine clearance between control and losartan-treated rats observed in the current study are also in line with results of previous studies [17][18][19][20][21][22]. Interestingly, we did not observe any differences in serum concentrations and urinary excretions of the electrolytes, albumin and protein between controls and losartan-treated rats (Tables 2 and 3), in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…The lack of differences in food intake, urine output and creatinine clearance between control and losartan-treated rats observed in the current study are also in line with results of previous studies [17][18][19][20][21][22]. Interestingly, we did not observe any differences in serum concentrations and urinary excretions of the electrolytes, albumin and protein between controls and losartan-treated rats (Tables 2 and 3), in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…Vaginal Smears were collected daily during the last 12 days of modeling and stained with Giemsa stain and evaluated by light microscope to confirm PCOS induction. After modeling, experimental (PCOS) group ( n = 50) was randomly divided into five equal groups as follows: a) PCOS group (DHEA; no treatment), b) DHEA + Telmisartan group (treated with 8 mg/kg telmisartan once daily by gastric tube for 28 days) (Cheng et al., 2018), c) DHEA + Fish oil group (treated with fish oil in a dose of 2.5 ml kg ‐1 day ‐1 once daily by gastric tube for 28 days) (Kabel, Abd Elmaaboud, & Albarraq, 2015), d) DHEA + CMC solution once daily by gastric tube for 28 days; and e) DHEA + Telmisartan +Fish oil group (treated with telmisartan concomitantly with fish oil in the above‐mentioned doses for 28 days).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the inhibitors of AT1 receptors remain as an important drug class in managing the hypertension development. 38,39 Moreover, previous studies reported markedly reduced NPs levels in patients with MetS, highlighting the importance of these peptides for homeostatic maintenance of BP levels. 40 In that sense, beneficial effect of Sac/Val, as neprylisine/AT1 receptor inhibitors, on BP and HR values may be linked to its physiological action on cardiovascular system.…”
Section: Discussionmentioning
confidence: 94%